The Effect of Information Technology and Understanding of Government Accounting Standards on the Quality of Financial Reports at the Marine and Fishery Services Bengkulu Province - Tia Suriyenti Putri; Oni Yulianti; Herlin Herlin (Journal of Indonesian Management, 2021)
The purpose of this study was to examine the effect of information technology and understanding of Government Accounting Standards on the quality of financial reports at the Bengkulu Province Marine and Fisheries Service. The sampling procedure used in this study is non-probability with purposive sampling technique, namely employees related to financial statements. Based on these criteria, the sample in this study was 30 employees at the Bengkulu Province Marine and Fisheries Service. Data collection methods using questionnaires and data analysis used is multiple linear regression, coefficient of determination and hypothesis testing. The regression results show a positive influence between information technology and understanding of Government Accounting Standards on the quality of financial reports at the Bengkulu Province Marine and Fisheries Service because the regression direction has a positive direction, namely Y = 2.062 + 0.436X1 + 0.670X2 + 5,504. Information technology has a significant effect on the quality of financial reports at the Bengkulu Province Marine and Fisheries Service, because the significant value of 0.005 is smaller than 0.05. Understanding of Government Accounting Standards has a significant influence on the quality of financial reports at the Bengkulu Province Marine and Fisheries Service because the significant value of 0.000 is smaller than 0.05. Information technology and understanding of Government Accounting Standards jointly have a significant effect on the quality of financial reports at the Bengkulu Province Marine and Fisheries Service because the significant value of 0.000 is smaller than 0.05. The coefficient of determination of R square is 0.603. This means that information technology and understanding of Government Accounting Standards affect the quality of financial reports by 60.3% while the rest (100-60.3% = 43.3%) is influenced by other causal factors not examined in this study..